Pelaksanaan proses asuhan gizi terstandar (PAGT) terhadap asupan gizi dan kadar glukosa darah pasien diabetes melitus tipe 2 - Yunita Yunita; Ahmad Husein Asdie; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Food planning is a basis of diabetes mellitus (DM) therapy. Proper diet is essential for effective control of blood glucose level. Diet therapy through the care of nutrition team in a hospital can increase nutrient intake of patients in a hospital. In 2003 the American Diabetes Association recommended a model of standardized nutrition care process (SNCP).Objective: To find out the effect of SNCP implementation to nutrient intake and blood glucose level of DM type 2 inpatients.Method: The study was a quasi-experiment. Nutrient intake variable was measured in post-test and blood glucose level variable was the pre-post test. Samples were divided into two groups; one group was treated with SNCP and the other with conventional nutrition care. The population of the study consisted of all new patients with DM type 2 diagnosis. Samples were those that met inclusion and exclusion criteria. Data were analyzed by using t-test.Results: Average nutrient intake was found high in the group with SNCP. Nutrient intake comprised energy intake (97.8%), protein intake (95.1%), fat intake (95.6%), and carbohydrate intake (94.9%). The result of the statistical test showed that nutrient intake (energy, protein, fat, carbohydrate) in SNCP was higher than that of conventional nutrition care. Decreasing blood glucose level before and after SNCP intervention was 109.4 mg/dL whereas in conventional nutrition care was 105.5 mg/dL. Decreasing blood glucose level of DM type 2 in patients with SNCP was higher than those with conventional nutrition care but statistically was not significant.Conclusion: Nutrient intake (energy, protein, fat and carbohydrate) of DM type 2 in the patient with SNCP were higher than those with conventional nutrition care. Decreased blood glucose level of DM type 2 in patients with SNCP was higher than those with conventional nutrition care, which was not statistically significant.